Moral Hazard : Does IMF Financing Encourage Imprudence by Borrowers and Lenders? - Phillips, Steven; Lane, Timothy (Washington, D.C. : International Monetary Fund, 2003)
Examines the issue of moral hazard inrelation to IMF loans to countries in financial difficulties. Concerns about moral hazard have had a prominent place in recent discussions on how the architecture of the international financial system should be reformed and what the IMF's role should be.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet